Bearing Capacity of Circular Footings on Confined Silty Sands - Kumar, Rajeev (My University, 2011)
There are vast deposits of silty sands along the banks of various rivers such as Indus, Ghaggar, Barinadi, Yammuna and Ganga. Among these deposits, river sand is obtained with different proportions of non-platic silts. As a result of varied investigations the engineering characteristics of sandy soils are well understood whereas not much efforts have been made to map the behavior of silty sands. Normally silty sands are obtained in a low to medium density states. This granular material needs to be characterized as an engineering material since it provides support to various structures such as structural rafts and deep foundations for multistoried buildings, excavations, tunnels and pipelines. In the present work, a set of standard tests are conducted to characterize the silty sands. They are x-ray diffraction, electron microscopy, grain size analysis, specific gravity, relative density and shear strength. The decreasing availability of good construction sites has increased use of sites with marginal soil properties. In view of this, the requirement for on site foundation systems to improve its bearing capacity and reduce the settlement has gone up significantly. The soil confinement is one such method to improve the bearing capacity and reduce the settlement of the footings on silty sands. The recent advancement in this field is to provide confinement to the soil by using metal cells and geocells. This technique of soil confinement, though successfully applied in some areas of geotechnical engineering, has not received much attention in foundation applications. In the Metropolitan cities all around the world, structures are constructed in a close proximity due to the non-availability of the land. The presence of structures around the footing under consideration simulates a condition similar to the existence of a skirt as considered in the present problem. The findings of our research are essentially to provide the lateral confinement by physical means and to extend its application to the buildings/ structures erected close to each other in the vicinity. If there are similar structures erected besides the central footing the effect implies confinement and the improvement in the bearing capacity. The settlement can be interpreted using a similar model as used by the author. The lateral confinement of soil is not really a direct means of soil improvement. It is a structural effect of the lateral confinement which really reduces the settlement of foundations on granular soils. The lateral confinement is v applied as cylindrical rings (just as a laboratory/experimental tools) below the footing. It results in to added stiffness of the soil which was referred as soil improvement. When the footing is loaded, such a cell resists the lateral displacements of soil underneath the footing and confines the soil leading to a significant decrease in the vertical settlement. The improvement factor of bearing capacity and settlement can be used as design charts which can be further improved for corresponding confining pressures. In the present work, experiments were performed to study the effect of silt and influence of cell confinement on the bearing capacity of circular footings on silty sand. Several laboratory experiments on clean sand and sand containing silt up to 25% were performed. The footings of 0.1m, 0.15m, 0.3m and 0.45m diameter supported on silty sands were investigated. For confinement of silty sand below the footing, cells of various sizes were used. The effect of proportion of silt in sand, cell diameter, cell height and the embedded depth of footing were investigated. For shallow footings on silty sands granular soils, scale effects were observed. The variation of bearing capacity factor (Nγ) with increase of footing diameter & fines content was obtained. Initially, the load settlement response of footings without cellular support was studied and thereafter, the results have been compared with that of footings with cellular support. It was observed that the bearing capacity of circular footings can be appreciably increased by soil confinement. It was interpreted that such confinement resists lateral displacement of soil underneath the footing that leads to significant reduction in settlement and improvement of bearing capacity of the footings significantly. The improvement in ultimate bearing capacity and reduction in settlement due to confinement have been represented using non-dimensional improvement factor (If) and settlement reduction factor (Sf) respectively. The cell–soil footing behaves as one unit for small cell diameters, while this pattern was no longer observed with large diameter cells. The results of model tests show that the bearing capacity decreases with increase of fines. With the increase of silt, the density increases but increase in compressibility offsets the effect of density. The cell height, depth, and diameter that gave the maximum improvement in bearing capacity have been presented and discussed.
Keywords: Confined Silty Sands